(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Cheiloscopy is a forensic investigation technique which deals with the study of grooves and furrows forming a characteristic pattern on the external surface of the lips. This is unique for every individual just like finger prints. Therefore, lip prints found at the scene of crime on drinking glass, cigarette ends, etc can be used to convict a suspect of crime. The aim of the study was to evaluate the depth of lip prints in identification, their uniqueness, consistency for a period of time and variation in males and females. Lip prints of 100 students, 50 males and 50 females of FMH College of Medicine and Dentistry, Lahore of the age group 18-23 years were collected and classified according to classification proposed by Suzuki. According to our study, Type I (40%) was the commonest pattern and Type I’ (6%) the least. This study revealed that lip print patterns are different in both sexes. Type I (56%) was commonest in females whereas Type V (1%) was the rarest. On the contrary, Type IV was predominant and Type I’ (2%) had the least frequency in males. This study showed that lip prints have a role in establishing personal identity as they are unique, permanent, show gender variation and remain unchanged during the life of an individual.